If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x = (x + 4) Reorder the terms: -2x = (4 + x) Remove parenthesis around (4 + x) -2x = 4 + x Solving -2x = 4 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -2x + -1x = 4 + x + -1x Combine like terms: -2x + -1x = -3x -3x = 4 + x + -1x Combine like terms: x + -1x = 0 -3x = 4 + 0 -3x = 4 Divide each side by '-3'. x = -1.333333333 Simplifying x = -1.333333333
| 9z^2-18z+8=0 | | 3(8+2x)=90 | | 4x^3+24x^2+32x=0 | | -2(3x-3)+8x-4= | | -2(8n-3)=-106 | | -3x-6-8x=12-3x-7 | | -2(x+5)=6-2x | | 8k+80=4k | | 19-5/x=34 | | (3)(2)+5/9 | | -2k-2(7k+2)=-(4+4k) | | 8.5/25.52 | | -108=-4(7v-8) | | 8-(2k+2)=-26-6k | | 3(x-7)=21+3x | | 3*2+5/9 | | 4+0.14x=8 | | 17y+15=49 | | x=(x+2) | | x^5-6x+7=0 | | 8-y/11=12 | | f(x)=3x+4andg(x) | | 7x-10=5x-26 | | X-2=-18 | | f(x)=3x+4and | | -3a/2=-1 | | -7(4-3x)=119 | | 4y=-8-8 | | 2=(x+y) | | X+-9=7 | | 12-9x-10=12 | | 13y/21-5/7 |